Pesantren Online: Pergeseran Otoritas Keagamaan di Dunia Maya - Qudsy, Saifuddin Zuhri (UIN Sunan Kalijaga Yogyakarta, 2019)
The cyberspace has been causing disruption in various aspecs of people's lives and institutions, including pesantren. This oldest religious institution in Indonesia has also redefined its meaning, thereby constructing a new stream called